Rapid Method for Estimation of Total Chlorophyll, Chlorophyll a and b and Carotene Content in Leaves of Cassava and Sweet potato Using SPAD Meter - Koshy, Anitha M; Joseph, Varsha; Ravi, V; Byju, G (JOURNAL OF ROOT CROPS, 2018)
A rapid, non-destructive method for determining total chlorophyll, chlorophyll a and b and carotene content in leaves of cassava and sweet potato using SPAD (Soil Plant Analysis Development) meter readings was developed at Central Tuber Crops Research Institute, Thiruvananthapuram, India. In cassava leaves, the SPAD readouts varied between 31.4 and 55.9 whereas in sweet potato leaves it varied between 22.1 and 47.8. In cassava leaves, the total chlorophyll, chlorophyll a, chlorophyll b, carotenoid and nitrogen content varied between 2.12 and 4.72 mg g-1, 1.53 and 3.71 mg g-1, 0.54 and 2.95 mg g-1, 0.34 and 0.8 mg g-1 and between 1.26 and 5.54% respectively. In sweet potato leaves, the total chlorophyll, chlorophyll a, chlorophyll b, carotenoid and nitrogen content varied between 0.58 and 1.69 mg g-1, 0.38 and 1.12 mg g-1, 0.2 and 0.5 mg g-1, 0.15 and 0.34 mg g-1 and between 1.4-4.77% respectively. The correlation between SPAD readings and total chlorophyll, chlorophyll a, chlorophyll b, carotenoid and nitrogen content, the coefficients of determination (R2) and the linear regression equations (y = a + bx) derived between SPAD readings and total chlorophyll, chlorophyll a and b, carotene and nitrogen content are given for cassava and sweet potato separately and together. The factors (F values) derived between SPAD readings and total chlorophyll, chlorophyll a and b and carotene and nitrogen content are given for cassava and sweet potato separately and together. The total chlorophyll, chlorophyll a and b and carotene content in leaves of cassava and sweet potato can be directly estimated by multiplying the SPAD readings with F values.